Reflections by an Educator on the Concept of Experience (Erlebnis) and the Movie Days of Nietzsche in Turin - Macelloni Alvarenga, Rosana Cristina [UNESP] (Univ Taubate, 2016)
This work is about reflections carried out by an educator on the concept of experience (Erlebnis) and the film Days of Nietzsche in Turin, in order to understand the concept of experience and your importance to people, not make more sense to dissociate Philosophy and Education and make it necessary another way of looking at human. In this sense, from Erlebnis concept, reading of Julio Bressane film brings the relationship of physical and psychological nature of a philosopher with the thinking of Nietzsche himself, who challenged humanity to think for yourself, move on with total freedom, proposed to overcome the human being himself, transcend ourselves and the incorporation of experiences, to form. Human experience is not pleasant in general and Nietzsche sought philosophical responses to the suffering of existence, pioneering a new way of thinking, it weakened our moral and religious beliefs and reminded us that life is there to build it, so that we build with our experiences ... this interpretation arose new questions and some answers in search of a better, more fruitful and more humane education.
Keywords: Experience; Nietzsche; Philosophy